Energy Resolved Tandem Mass Spectrometry Experiments for Resolution of Isobaric Compounds: A Case of Cis/Trans Isomerism. Issue 5 (October 2016) - Menicatti, Marta; Guandalini, Luca; Dei, Silvia; Floriddia, Elisa; Teodori, Elisabetta; Traldi, Pietro; Bartolucci, Gianluca
A series of N -alkanol- N -cyclohexanol amine aryl esters cis / trans isomers that showed high efficacy to reverse the acquired resistance of cancer cells during chemotherapeutic therapy (MDR mechanism) was studied. These compounds were two 1, 4 cyclohexane cis / trans derivatives (named ELF26A and ELF26B, respectively), and their positional isomers (named ELF34A and ELF34B, respectively) where the aryl-moieties were exchanged. In order to evaluate the behaviour of these compounds during biological tests, a method based on liquid chromatography coupled with mass spectrometry (LC-MS), operating in tandem mass spectrometry (MS/MS) mode, was developed. A unique chromatographic method suitable to separate the two pairs of cis / trans isomers was not achieved and the MS/MS experiments of the different compounds was not always able to characterise the different isomers. Therefore, a system of linear equations of deconvolution analysis (LEDA) tool was proposed to determine the relative proportions of individual cis / trans isomers in the sample. Considering the pharmaceutical interest of the compounds under investigation, the analytical method developed was tested to be effective at the active concentration levels, corresponding to a concentration of ng mL −1 of compound in a processed sample. Precision and accuracy of the LEDA algorithm at three levels of relative concentrations of analytes were checked, i.e. low-level (about 25% in the mixture), mid-level (about 50% in the mixture) and high-level (about 70% in the mixture). Evaluation of performances of the algorithm proved that the accuracy (between 88.3% and 99.9%) and precision (between 2.0% and 3.7%) for simultaneous analysis of the mixtures of the four isomers is feasible. It is worth highlighting that the choice of characteristic product ions and optimal abundance ratios plays an important role in the application of the LEDA approach. Therefore, performing an investigation on the energetics of fragmentation pathway allowed the selection of the better product ions for each analyte in terms of both sensitivity of detection and specificity, i.e. the capability to distinguish between isomeric compounds. Finally, the developed approach was applied to determine the relative proportions of individual cis / trans isomers in spiked human plasma samples. The results obtained confirm the reliability of the proposed method in biological samples as well.